Cross-sectional study of the prevalence and risk factors of metabolic syndrome in a rural population of the Qianjiang area. Issue 35 (28th August 2020) - Ling, Bing; Zhao, Li; Yi, Jixiu
Abstract : Abstract: The prevalence of the metabolic syndrome (MS) is increasing in China, but there are disparities between urban and rural populations, and across different regions. To examine the prevalence and risk factors of MS in the rural area of Qianjiang (Southwest China). From March 2016 to June 2018, 6 townships in the Qianjiang District of Chongqing Municipality were selected for a cross-sectional study of the residents in rural areas. Demographics and medical history were collected using a questionnaire. Anthropometry and blood pressure were obtained by physical examination. Blood lipids, fasting plasma glucose, and 2-h postprandial glucose were measured. A total of 2949 (1067 males and 1882 females) were included. The mean age was 63.8 ± 10.7 years. The prevalence of MS in the study population was 16.8% (496/2949). The prevalence of MS was 7.4% in men, 22.2% in women, 15.7% in Han, 18.1% in Tujia, and 14.8% in Miao. According to age, the prevalence of MS was 10.6%, 17.0%, and 18.3% in the 30–50, 50–69, and ≥ 70 years groups. The multivariable analysis showed that female sex (OR = 33.36, 95%CI: 17.0–65.53), dyslipidemia (OR = 4.71, 95%CI: 1.73–12.82), kidney diseases (OR = 2.32, 95%CI: 1.37–3.94), waistline (OR = 1.39, 95%CI: 1.33–1.46), high-density lipoprotein cholesterol (OR = 0.12, 95%CI: 0.06–0.23), triglycerides (OR = 1.52, 95%CI: 1.31–1.76), alanine aminotransferase (OR = 0.98, 95%CI: 0.97–1.00), γ-glutamyltransferase (OR = 1.00, 95%CI: 1.00–1.01), and glycated hemoglobin (OR = 1.31, 95%CI: 1.08–1.59) were independently associated with MS. The prevalence of MS was 16.8% in Qianjiang. Female sex, kidney diseases, alanine aminotransferase, and γ-glutamyltransferase were independent risk factors for MS.